Impact of Self-Concept, Self-Imagination, and Self-Efficacy on English Language Learning Outcomes Among Blended Learning Students During COVID-19 - Chen, Ruihua; Iqbal, Javed; Liu, Yanghe; Zhu, Mengmei; Xie, Yi (Frontiers in Psychology, 2022)
The purpose of the present study was to explore the direct influence of self-concept and self-imagination on English language learning outcomes (ELLO). Furthermore, this study examined the mediating role of self-efficacy in the relationship between self-concept, self-imagination and English language learning outcomes. A survey questionnaire comprised of 21 items was used in this study. We distributed the questionnaire through QR code and collected the data from 2517 participants who enrolled in blended learning courses at the undergraduate level in Chinese universities. The relationship among variables was measured through SmartPLS-SEM 3.3.3 (Partial least squares structural equation modeling). The outcomes of the present study indicated a direct, positive and significant connection of self-concept, self-imagination and self-efficacy with English language learning outcomes. Looking at indirect influences, self-concept and self-imagination positive and significant influence English language learning outcomes through self-efficacy. Thus, self-efficacy was indicated to play a mediating role between self-concept, self-imagination and English language learning outcomes. We can conclude that self-concept, self-imagination, and self-efficacy are the main predictors of English language learning outcomes in blended learning courses during the pandemic. Additionally, self-concept and self-imagination along with the intervening role of self-efficacy, play a more effective role in improving English language learning outcomes. Moreover, this study provided some useful, practical implications and future research directions.